2010
DOI: 10.1097/coc.0b013e31819fdf7c
|View full text |Cite
|
Sign up to set email alerts
|

Cine-Magnetic Resonance Imaging Assessment of Intrafraction Motion for Prostate Cancer Patients Supine or Prone With and Without a Rectal Balloon

Abstract: Intrafraction prostate motion was found dependent on time, patient position, and the use of a rectal balloon. Relatively stable positions can be obtained for 4 minutes or less especially in the supine position with a rectal balloon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 26 publications
4
33
1
Order By: Relevance
“…Formal analysis of random and systematic variation was not performed in this study because the only repeated analysis is for the same patient in a different position. In the paper by Vargas et al, ( 17 ) random variation was correlated to the standard deviations (as in our Table 2) and systematic variations to the vector means (as in our Table 1). Finally, we did not attempt to assess the dosimetric consequences of the long‐term or short‐term displacements.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Formal analysis of random and systematic variation was not performed in this study because the only repeated analysis is for the same patient in a different position. In the paper by Vargas et al, ( 17 ) random variation was correlated to the standard deviations (as in our Table 2) and systematic variations to the vector means (as in our Table 1). Finally, we did not attempt to assess the dosimetric consequences of the long‐term or short‐term displacements.…”
Section: Discussionsupporting
confidence: 62%
“…1 and 2, comparing both positions. Vargas et al ( 17 ) applied automatic deformable segmentation of the prostate to seven patients in prone and supine positions to identify centroid motion in the sagittal plane using 4‐minute cine magnetic resonance imaging at 0.4 Hz. The Vargas study found mean displacements in the SI and AP planes similar to our results, but its mean SDs were considerably larger than the values we report in Table 2, and Vargas and colleagues found the SDs in the AP plane to be much greater than in the SI plane, compared to our finding of similar magnitude between the two planes.…”
Section: Discussionmentioning
confidence: 99%
“…However, when an ERC is not used, the prone position may be a better alternative for some men. Imaging patients in the prone position can result in higher respiratory motion artifacts but may be necessary to facilitate comfort for certain patients [45,46]. MR imaging of the prostate begins with a low-resolution 3-plane localizer 'scout.'…”
Section: Protocolsmentioning
confidence: 99%
“…However, it has recently become clear that prostate motion occurs in accordance with the respiratory cycle (2)(3)(4)(5). Therefore, the respiratory-induced motion of the prostate may be considered a factor in locating and reducing intrafraction motion during treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown, using implanted radiopaque prostate markers and fluoroscopy, that ventilatory movement in the prostate is substantial in the prone position (2)(3)(4). A study using cine-magnetic resonance imaging (cine-MRI) also demonstrated that the amplitude of the respiratory-induced motion in the supine position is smaller than that in the prone position (5).…”
Section: Introductionmentioning
confidence: 99%